Millard’s Rotation Advancement Technique: Advancements and Clinical Applications in Cheiloplasty - Mohd. Altaf Mir; Jaya Jain (Key Flaps in Plastic Surgery, 2023)
This book chapter focuses on Millard’s Rotation Advancement Cheiloplasty, a widely used surgical technique for repairing cleft lip. A case presentation is provided, describing a child with a left complete cleft lip and palate. The diagnosis is a left complete cleft lip and palate, classified as Modified Kernhan’s 10-19 and Veau group III. The operative procedure involves marking for Millard’s rotation advancement cheiloplasty, followed by flap preparation and the freeing of abnormal orbicularis orris muscle attachments. Muscle, skin, and mucosal approximation are performed to close the cleft lip. The postoperative period remains uneventful, and satisfactory results are observed during follow-up examinations. The discussion section introduces Millard’s Rotation Advancement Cheiloplasty, highlighting its purpose in repairing cleft lip by rotating and advancing tissue to achieve closure and restore normal lip contour. The surgical techniques involved in the procedure are described, including patient evaluation and planning, anaesthesia, incision and exposure, tissue mobilization and rotation, tissue advancement and closure, and postoperative care. Advantages of Millard’s Rotation Advancement Cheiloplasty include aesthetic improvement, functional improvement, long-term stability, and minimized scarring. The limitations of the technique, such as the need for an individualized approach and multidisciplinary care, are also discussed. Potential complications associated with the procedure are mentioned, emphasizing the importance of proper preoperative evaluation, surgical technique, and postoperative care. The abstract emphasizes the practical application of Millard’s Rotation Advancement Cheiloplasty in repairing cleft lip and the benefits it provides in terms of aesthetics, lip function, and long-term stability. By understanding the surgical technique and considering the advantages and limitations of the procedure, healthcare professionals can effectively address cleft lip and contribute to the overall well-being and development of affected individuals.